Community Based Forest Rehabilitation Through Incentive Mechanism: A Case Study in Solok and Agam District, West Sumatra - Mutolib, Abdul; Yonariza, Yonariza; Mahdi, Mahdi (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The existence of forests is essential to human living on earth, but the existence of forest is threatened by deforestations and forest degradations. Forest rehabilitation programs that have been carried out by the government and other parties often fail. Different approaches are needed to improve the success of forest rehabilitation in Indonesia. This research aims to analyze the success of community-based forest rehabilitation through the forest incentive and the factors that influence it. The site is in Nagari Paninggahan Solok District and in Nagari Kamang Agam District, West Sumatra. The location is part of Voluntary Carbon Market (VCM) projects by CO2BV company from the Netherlands. The research and the data collection were conducted in April 2017. Data types that were used in this research were primary and secondary data. The data analysis techniques used were descriptive qualitative analysis. The results showed that community-based forest rehabilitation through an incentive system has been successful to improve the condition of degraded forests in the research site. The indicators of the success of this program were the increase of variety and number of trees, the level of trees density, and the increase of water supply in the surrounding areas of the rehabilitation zones. The success program was affected by several factors, those were: 1) community institutions (farmers group), 2) the clarity of contract and intensive mechanism, 3) mentoring and supervisions, 4) the clarity of benefits for the citizens, 5) community participation, and 6) the communication among stakeholders. It is expected that this research can provide an insight for the government in policy-making to rehabilitate degraded forests. This finding provides information that the government needs to consider the economic aspects of local communities in forest rehabilitation programs. the incentive is one of the important factors that support the success of forest rehabilitation